The Critical Role of Faecalibacterium prausnitzii in Cardiovascular Diseases - Tiantian Zheng; Chenchen Meng; Zhengtian Lv; Chenxia Wu; Xinbin Zhou; Wei Mao (Reviews in Cardiovascular Medicine)
Due to the continued aging of the global population, cardiovascular diseases (CVDs) remain the main cause of death worldwide, with millions of fatalities from diseases, including stroke and coronary artery disease, reported annually. Thus, novel therapeutic approaches and targets are urgently required for diagnosing and treating CVDs. Recent studies emphasize the vital part of gut microbiota in both CVD prevention and management. Among these, Faecalibacterium prausnitzii (F. prausnitzii) has emerged as a promising probiotic capable of improving intestinal health. Although preliminary investigations demonstrate that F. prausnitzii positively enhances cardiovascular health, research specifically connecting this strain to CVD outcomes remains limited. Based on current research and assessment of possible clinical applications, this paper aimed to investigate the positive effects on cardiovascular health using F. prausnitzii and its metabolites. Targeting gut flora is expected to become a mainstay in CVD treatment as research develops.